Pengaruh Partisipasi Masyarakat, Akuntabilitas, Transparansi Kebijakan Publik, Kompetensi Sumber Daya Manusia, dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Kasus Pemerintah Daerah Kota Tegal) - Mahmudah, Nurul; Faidah, Yusri Anis (Prisani Cendekia, 2025)
This research aims to examine the influence of community participation, accountability, public policy transparency, Human Resource Competency, Use of Information Technology on the Quality of Tegal City Regional Government Financial Reports. This research is quantitative research using primary data through direct observation and questionnaires to respondents. The data analysis method uses multiple linear regression analysis with independent variables, namely community participation, accountability, public policy transparency, human resource competence, and use of information technology. Meanwhile, the dependent variable is the quality of financial reports. The population in this study were all employees in 37 OPDs in the Tegal City Government. This research is quantitative research that uses primary data from distributing questionnaires as a data source. The sample was determined based on purposive sampling techniques. The results of the research show that public participation has no partial effect on the quality of financial reports, accountability has a partial effect on the quality of financial reports, public policy transparency has no partial effect on the quality of financial reports, Human Resources competency has no partial effect on the quality of financial reports, utilization Information technology partially influences the quality of financial reports as well as public participation, accountability, transparency of public policies, Human Resources competence, and the use of information technology simultaneously influence the quality of financial reports